Characterization of silicon photodiodes for diffuse reflectance signal extraction - Pimenta, Sara (2015)
Early detection of gastrointestinal (GI) cancers is one of most important concerns in medical field. Its detection at the earliest stage is crucial to increase the patient survival chances. Optical signals extraction and analysis, specifically diffuse reflectance and intrinsic fluorescence, may improve the ability to detect GI dysplasia, once some morphological and biochemical changes on the tissues (related with early cancer progression) can modify these signals' shape and intensity. The project under this paper aims to develop a chip-sized spectroscopy microsystem for the early detection of GI cancer. This paper presents the characterization of different dimensions pn-junction silicon photodiodes (n+/p-epilayer type) fabricated in a standard 0.7 mu m CMOS process. An array comprising 16 of those photodiodes must be implemented for the diffuse reflectance and intrinsic fluorescence signals measurements. The main goal is to conclude about the photodiodes minimum dimensions, taking into account its capacity to extract the signals in the relevant spectral band (350 nm - 750 nm), not comprising the microsystem dimensions. With this study, it can be concluded that a 100 x 100 mu m(2) active area presents a quantum efficiency suitable to extract diffuse reflectance signals, which was proven using a test phantom representative of a GI tissue.